Need Assessment Survey Of The Expected Skill Types Of Graduates Of Semarang Health Polytechnic - Marsum Marsum; Arwani Arwani; Supriyana Supriyana (UPPM Poltekkes Kemenkes Semarang, 2015)
The aim of the research was to examine the expected skill types of graduates of Semarang Health Polytechnic. A quantitative research by applying survey was conducted to 17 samples (users) used a purposive sampling technique.Research results showed that users more expected to graduates to have soft skills in term of honesty, discipline, and communication skills. Furthermore, users also hoped that the graduates should be able to speak in foreign languages, have more training, and be capable in operating information and technology. In addition, users requested to the graduates to have particular skills such as wound care (diabetic wound care), hypnobirthing, pest control, catering diet, and radiation protection officer. It is recommended to the management of Semarang Health Polytechnic to set soft skills as local capacity as well as add some particular skills to be a part of certification in each department.